2011
DOI: 10.1016/j.mambio.2010.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Topography is a limiting distributional factor in the soprano pipistrelle at its latitudinal extreme

Abstract: a b s t r a c tClimatic conditions such as temperature and seasonality are becoming increasingly harsh towards the latitudinal extreme of the distribution and may limit the occurrence of mammals through decreased food availability or accessibility. For nocturnal bats increasing day length in summer may also limit the range latitudinally.We investigated the effect of long term mean temperature, precipitation, altitude, water affinity, terrestrial habitat, and topography on the summer distribution of the soprano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…The important effect of temperature on diversity as found in this study was highly anticipated based on general theories on bat distribution (Kaufman andWillig 1998, Ulrich et al 2007, see also Michaelsen et al 2011). However, common occurrence of northern bats in alpine habitats and the relatively wide distribution of other species were not expected.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…The important effect of temperature on diversity as found in this study was highly anticipated based on general theories on bat distribution (Kaufman andWillig 1998, Ulrich et al 2007, see also Michaelsen et al 2011). However, common occurrence of northern bats in alpine habitats and the relatively wide distribution of other species were not expected.…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, all areas studied have tall mountains blocking out the sun well before sunset and after sunrise. This factor can influence bat distribution and behaviour at these latitudes (Michaelsen et al 2011). Available publications from the study area (Gjerde and Fuszara 1995, Olsen 1996, Michaelsen 2003, 2012, 2004a,b, Michaelsen and van der Kooij 2006, Isaksen et al 2009 suggest that bats can be found in all available landscapes and habitats, ranging from alpine areas to coastal plains with only bracken vegetation, cliffs, cities, roads (street lamps), cultivated areas, freshwater and marine shores, woodlands (all sorts), coastal islands and more.…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations